Freemium Monetization and User Psychology in Short-Form Drama Mobile Applications: A Study of Payment Behavior and Satisfaction - Rizaldi Akbar; Fauzan Putraga Al Bahri; Bahruni Bahruni; Yonoriadi Yonoriadi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines payment behavior and user satisfaction among Indonesian short drama app users operating under aggressive freemium models with pay-per-episode mechanisms. Using a mixed-method approach with 240 active users across 12 applications (DramaBox, ReelShort, ShortMax, MoboReels, FlexTV, and others), the research investigates psychological factors influencing willingness to pay, actual spending patterns, and post-purchase regret. Results reveal that most users are Millennials and Gen Z (76.6% aged 18-34 years) exhibiting strong binge-watching patterns (averaging 10-11 episodes per session). TikTok serves as the primary drainage platform, accounting for 63.3% of user acquisition. The conversion rate reaches 41.2% with average monthly spending of Rp 116,003, yet exposes a paradox: Indonesia leads global downloads while demonstrating disproportionately low monetization. Regression analysis identifies Perceived Content Quality (β=0.324) and Perceived Enjoyment (β=0.245) as the strongest predictors of willingness to pay, whereas Perceived Cost Fairness shows a significant negative effect (β=-0.257). Impulse Buying emerges as the sole significant differentiator between paying and non-paying users. Path analysis reveals the SOR model's inadequacy, with direct effects dominating—particularly Customer Satisfaction on Intention to Continue (β=0.564). Although 80% of respondents recognize psychological manipulation tactics, awareness does not diminish their effectiveness. The study underscores the need for regulatory frameworks balancing innovation with consumer protection against aggressive monetization tactics that potentially exploit vulnerable users.